1994
DOI: 10.1007/bf02334203
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of dissolved oxygen levels in a hypertidal estuary by sediment resuspension

Abstract: Hyperconcentrated benthic layers, which form during neap tides, recruit much of the fine sediment population of the turbidity maximum of a hypertidal estuary. Measurements of tidal amplitude and suspended solids concentration reveal that resuspension of the hyperconcentrated layers occurs between three and eight tides after neap tides rather than during spring tides (12 to 15 tides after neaps). During these resuspension events, dissolved oxygen levels are reduced but recover by spring tides. Peak solids conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Moreover, the rapid oxygen depletion of the water in the summer is particularly marked in the Loire Estuary (Thouvenin et al, 1994), although it occurs in all three studied estuaries; resuspension of anoxic ''fluid mud'' at spring tides, i.e. benthic layers with a high TSS concentration (one to several hundred g l -1 ), appears to be the main reason for the hypoxia (Abril et al, 2003(Abril et al, , 2004), as reported for several other macrotidal estuaries (Parker et al, 1994;Uncles et al, 1998).…”
Section: Study Areamentioning
confidence: 76%
“…Moreover, the rapid oxygen depletion of the water in the summer is particularly marked in the Loire Estuary (Thouvenin et al, 1994), although it occurs in all three studied estuaries; resuspension of anoxic ''fluid mud'' at spring tides, i.e. benthic layers with a high TSS concentration (one to several hundred g l -1 ), appears to be the main reason for the hypoxia (Abril et al, 2003(Abril et al, , 2004), as reported for several other macrotidal estuaries (Parker et al, 1994;Uncles et al, 1998).…”
Section: Study Areamentioning
confidence: 76%
“…Organic carbon budget calculations showed that one-half of the POC entering the MTZ is mineralized within the estuary, the rest being exported to the Atlantic Ocean or sedimented in the estuary (Etcheber 1983;Lin 1988). Oxygen concentrations in surface waters are relatively high, compared to other macrotidal turbid estuaries (Morris et al 1982;Wollast 1983;Parker et al 1994;Thouvenin et al 1994), with concentrations close to saturation levels in riverine and marine parts and about 40-60% of saturation in the MTZ (IFREMER 1994, unpubl. data).…”
Section: Methodsmentioning
confidence: 99%
“…Two superimposed cycles of sedimentation and resuspension coexist: neap tides are sedimentation periods, whereas spring tides are dominated by erosion (15-d lunar cycle). Moreover, high-and low-water slacks are sedimentation periods, whereas midebb and midflood are erosion periods (semidiurnal cycle) (Inglis and Allen 1957;Allen et al 1980;Le Hir and Karlikow 1991;Parker et al 1994;Reed and Donovan 1994;Grabemann et al 1997). During neap-tide minimum energy periods, surface turbidities are considerably lower, and hyperconcentrated benthic layers (named ''fluid mud'' by Inglis and Allen 1957) accumulate on the bottom.…”
mentioning
confidence: 99%
See 2 more Smart Citations